RETRACTED: Comparison of Single and Hybrid Coastal Protection Systems for Tsunami Wave Attenuation Using a Pneumatic Simulator - Herdiana Mutmainah (JURNAL TEKNIK HIDRAULIK, 2025)
Following a rigorous and carefully considered review by the Editorial Board of Jurnal Teknik Hidraulik regarding the article entitled:“Comparison of Single and Hybrid Coastal Protection Systems for Tsunami Wave Attenuation Using a Pneumatic Simulator” Published in: Jurnal Teknik Hidraulik, Vol. 16, No. 1, pp. 1–12, June 2025 DOI: https://doi.org/10.32679/jth.v16i1.797. This paper has been found to be in violation of the publication ethics and principles of Jurnal Teknik Hidraulik and has therefore been formally retracted.The editorial investigation, prompted by a formal complaint from the Research Center for Hydrodynamic Technology (PRTH) – BRIN, concluded that the article:Contains research data and results from a team project at PRTH (2022–2023),Was published without authorization or acknowledgment of the original data owners (specifically Dr. Widjo Kongko as Principal Investigator),Incorrectly stated the author’s affiliation as PRTH–BRIN despite no longer being part of the institution since early 2024,Was submitted and published as a single-author article although it derived from a collaborative team effort.These findings represent serious breaches of academic integrity, data ownership rights, and authorship ethics. As a result, the document and its content have been removed from the Jurnal Teknik Hidraulik website, and reasonable efforts should be made to remove all references to this article from citations, bibliographic databases, and future scholarly use.We apologize to our readers and the academic community for any inconvenience this may have caused.